2009
DOI: 10.1111/j.1540-8175.2009.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Function and Tei Index by Tissue Doppler Imaging in Patients with Slow Coronary Flow

Abstract: LV systolic and diastolic function is impaired in patients with SCF. TDI analysis of mitral annular velocities such as the Tei index, Em, Em/Am, and Sm is useful to assess LV systolic and diastolic dysfunction in patients with SCF. Mean TFC and RCA TFC were positively correlated with the Tei index and LCX TFC was negatively correlated with Em/Am. TDI may be better than conventional echocardiography in assessing LV function in patients with SCF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
4
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 21 publications
(26 reference statements)
5
45
4
2
Order By: Relevance
“…15 Baykan et al showed that both systolic and diastolic functions are impaired in patients with CSFP by tissue Doppler imaging analysis of mitral annular velocities. 16 Our study failed to show an association between slow flow and diastolic function. The differences in the studied populations may account for this discrepancy.…”
Section: Diastolic Dysfunction and Csfpcontrasting
confidence: 47%
“…15 Baykan et al showed that both systolic and diastolic functions are impaired in patients with CSFP by tissue Doppler imaging analysis of mitral annular velocities. 16 Our study failed to show an association between slow flow and diastolic function. The differences in the studied populations may account for this discrepancy.…”
Section: Diastolic Dysfunction and Csfpcontrasting
confidence: 47%
“…The relationship between CSFP and pro-BNP was not assessed previously. Baykan et al (24) evaluated diastolic function by tissue Doppler technique and found a positive correlation with mean TIMI frame count in patients with CSFP. In our study, the relationship a positive correlation between proBNP and TIMI frame count was determined in patients with CSFP supporting the results of Baykan et al (24).…”
Section: Discussionmentioning
confidence: 99%
“…KYA tespit edilen hastalarda sağlıklı grupla kıyaslandığında sistolik ve diyastolik fonksiyon bozukluğu geliştiği nabız dalgalı Doppler ve doku Doppler yöntemleri ile gösterilmiştir (4) . Baykan ve arkadaşları tarafından yapılan çalışmada geleneksel ekokardiyografi parametrelerinde (E, A, E/A, DT ve IVRT) KYA fenomeni ile kontrol grubu arasında anlamlı fark saptanmamıştır (12) . Zencir ve arkadaşları tarafından yapılan başka bir çalışmada ise ekokardiyografik olarak bakılan sol ventrikül sistolik ve diyastolik fonksiyonların kontrol grubundan farklı bulunmadı-ğı saptanmıştır (13) .…”
Section: Discussionunclassified